Assessment of exposure to Vibrio in shellfish consumed in Abidjan, Côte d'Ivoire - Traoré, S.; Costard, Solenne; Krabi, R.; Odermatt, P.; Utzinger, J.; Makita, K.; Grace, Delia; Koussemon, M.; Bonfoh, Bassirou (Centre Suisse de Recherches Scientifiques, 2012)
The consumption of shellfish contaminated with Vibrio spp. is a cause of serious food borne diseases (FBD) and a concern in Abidjan where shellfish are mostly purchased on informal markets. This study assessed the risk of exposure to Vibrio spp. via the consumption of shellfish in Abidjan using stochastic modelling. Parameters were derived from 3 studies: Vibrio spp. prevalence in shellfish (n=322) at markets, household survey (n=120) and focus group discussions (n=8) on consumers’ practices. Both non-parametric bootstrapping and parametric distributions were used to represent uncertainty. The model was implemented in ModelRisk, using Monte Carlo simulation with 5,000 iterations. The incidence rate of consumption of shellfish contaminated by Vibrio spp. at the time of purchase was 5 per person year [90% CI=2.7; 7.3]. The prevalence of Vibrio spp. in shrimp and crab were 10.5% and 6.9%, respectively. The main parameter influencing the exposure was Vibrio spp. prevalence in crab, followed by the daily rate of consumption of shellfish. Shellfish consumption was daily for 11.7% of households, occasional for 45.8% and rare for 42.5%. Hazard and risk characterization are ongoing to estimate the risk of FBD associated with the consumption of contaminated shellfish. Results from the household survey showed that 7.5% of respondents reported symptoms of food poisoning. Shellfish are consumed boiled (96.7%) or fried (3.3%); reported cooking times varied from 5-15 min (6.8%) to more than an hour (64.2%). Although shellfish cooking practices seem to limit the risk of FBD, findings from focus group discussions suggest cross-contamination of vegetables and other food items consumed raw might happen.